The absurdity of existence: Analyzing human relationships in Sartre's No Exit - Abdlalla, Shabaz A.; Muhammed, Rebwar Z.; Ahmad, Hedayat M. (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
This article explores the philosophical concepts of existentialism and absurdism, focusing on the works of Jean-Paul Sartre and Albert Camus. It begins by examining Sartre's notion of